Metals on the Menu—Analyzing the Presence, Importance, and Consequences - Vedran Milanković; Tamara Tasić; Andreja Leskovac; Sandra Petrović; Miloš Mitić; Tamara Lazarević-Pašti; Mirjana Novković; Nebojša Potkonjak (Foods, 2024)
Metals are integral components of the natural environment, and their presence in the food supply is inevitable and complex. While essential metals such as sodium, potassium, magnesium, calcium, iron, zinc, and copper are crucial for various physiological functions and must be consumed through the diet, others, like lead, mercury, and cadmium, are toxic even at low concentrations and pose serious health risks. This study comprehensively analyzes the presence, importance, and consequences of metals in the food chain. We explore the pathways through which metals enter the food supply, their distribution across different food types, and the associated health implications. By examining current regulatory standards for maximum allowable levels of various metals, we highlight the importance of ensuring food safety and protecting public health. Furthermore, this research underscores the need for continuous monitoring and management of metal content in food, especially as global agricultural and food production practices evolve. Our findings aim to inform dietary recommendations, food fortification strategies, and regulatory policies, ultimately contributing to safer and more nutritionally balanced diets.